2021
DOI: 10.5653/cerm.2020.03706
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms in the ESR2 and FSHR genes with poor ovarian response in infertile Jordanian women

Abstract: Objective: Poor ovarian response (POR) refers to a subnormal follicular response that leads to a decrease in the quality and quantity of the eggs retrieved after ovarian stimulation during assisted reproductive treatment (ART). The present study investigated the associations of multiple variants of the estrogen receptor 2 (ESR2) and follicle-stimulating hormone receptor (FSHR) genes with POR in infertile Jordanian women undergoing ART.Methods: Four polymorphisms, namely ESR2 rs1256049, ESR2 rs4986938, FSHR rs6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The previous study showed that some young normogonadotrophic patients were to be unexpected hypo-response in standard GnRHa long protocol. [ 12 ] At present, ovarian hypo-response in assisted reproduction technology remains to be elucidated, increasing evidence suggests that the presence of genetic mutations or single nucleotide polymorphisms of gonadotropins and their receptors could influence ovarian sensitivity to gonadotropin stimulation, which may need more starting dose of FSH and total consumption of FSH during COS. [ 13 ] But, the selection of starting dose FSH in long-term GnRH-agonist protocol depended on age, weight, anti-Müllerian hormone, and antral follicle number, which also should decrease ovarian hyperstimulation syndrome risk. [ 14 ] In this study, starting doses did not differ significantly between the +LE group (225 [150–225]/day) and the +Gn group (200 [150–225]/day).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that some young normogonadotrophic patients were to be unexpected hypo-response in standard GnRHa long protocol. [ 12 ] At present, ovarian hypo-response in assisted reproduction technology remains to be elucidated, increasing evidence suggests that the presence of genetic mutations or single nucleotide polymorphisms of gonadotropins and their receptors could influence ovarian sensitivity to gonadotropin stimulation, which may need more starting dose of FSH and total consumption of FSH during COS. [ 13 ] But, the selection of starting dose FSH in long-term GnRH-agonist protocol depended on age, weight, anti-Müllerian hormone, and antral follicle number, which also should decrease ovarian hyperstimulation syndrome risk. [ 14 ] In this study, starting doses did not differ significantly between the +LE group (225 [150–225]/day) and the +Gn group (200 [150–225]/day).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation makes a noteworthy contribution to ovarian response. Single nucleotide polymorphisms have been identified in genes with key roles in oogenesis, folliculogenesis, and female reproduction, such as in estrogen receptor 2 ( ESR2 ), follicle-stimulating hormone receptor ( FSHR ), FSH β-chain ( FSHB ), luteinizing hormone β-chain ( LHB ), LH/choriogonadotropin receptor ( LHCGR ), growth differentiation factor-9 ( GDF9 ), anti-Müllerian hormone ( AMH ), and AMH type II receptor ( AMHR2 ) genes [ 31 34 ]. However, the usefulness of sequence variants in clinical practice is limited due to inconclusive results from population-based studies [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FSHR SNPs, including A2039G (rs6166), are the most common studied genetic variants related to ovarian response in ART treatment [ 16 , 17 , 18 , 19 , 20 , 21 ]. A recent meta-analysis indicated that FRHR rs6166 is associated with premature ovarian insufficiency (POI) in an Asian population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AMH 146 T > G is at the coding region of AMH and causes amnio acid substitution. FSHR Asn680Ser (rs6166) is the most common reported SNP that related to ovarian responses in ART cycles [ 16 , 17 , 18 , 19 , 20 , 21 ]. GnRH (rs6185) and GnRHR (rs3756159) are chosen to discriminate the different activities of GnRHa and GnRHanta in ART treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation